2014
DOI: 10.3389/fnhum.2014.00251
|View full text |Cite
|
Sign up to set email alerts
|

Distant functional connectivity for bimanual finger coordination declines with aging: an fMRI and SEM exploration

Abstract: Although bimanual finger coordination is known to decline with aging, it still remains unclear how exactly the neural substrates underlying the coordination differ between young and elderly adults. The present study focused on: (1) characterization of the functional connectivity within the motor association cortex which is required for successful bimanual finger coordination, and (2) to elucidate upon its age-related decline. To address these objectives, we utilized functional magnetic resonance imaging (fMRI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 76 publications
2
13
1
Order By: Relevance
“…Recent aging studies have focused on activity of the cerebral cortex, and have made some progress in determining the role of age-related functional brain changes in bimanual performance declines (Goble et al, 2010;Heitger et al, 2013;Kiyama, Kunimi, Iidaka, & Nakai, 2014;Solesio-Jofre et al, 2014). Other aging studies have demonstrated a significant role of microstructural changes in white matter structures and particularly the corpus callosum (Fling et al, 2011;Gooijers & Swinnen, 2014;Serbruyns et al, 2013;Sullivan et al, 2001), the largest white matter tract connecting interhemispheric cortical regions (Jarbo, Verstynen, & Schneider, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent aging studies have focused on activity of the cerebral cortex, and have made some progress in determining the role of age-related functional brain changes in bimanual performance declines (Goble et al, 2010;Heitger et al, 2013;Kiyama, Kunimi, Iidaka, & Nakai, 2014;Solesio-Jofre et al, 2014). Other aging studies have demonstrated a significant role of microstructural changes in white matter structures and particularly the corpus callosum (Fling et al, 2011;Gooijers & Swinnen, 2014;Serbruyns et al, 2013;Sullivan et al, 2001), the largest white matter tract connecting interhemispheric cortical regions (Jarbo, Verstynen, & Schneider, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This interlimb interference appears to alter with aging. Indeed, studies have demonstrated that bimanual coordination is less accurate and/or more variable in older compared to young adults (Temprado et al, 2010 ; Solesio-Jofre et al, 2014 ), particularly for the anti-phase pattern (Wishart et al, 2000 ; Lee et al, 2002 ; Bangert et al, 2010 ; Summers et al, 2010 ; Fling et al, 2011 ; Kiyama et al, 2014 ). However, this age effect appears to be more pronounced in intermittent than continuous tasks (Bangert et al, 2010 ; Summers et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Older adults demonstrated increased sensorimotor resting state functional connectivity, in which reductions in bimanual performance strongly related to increases in premotor functional connectivity [68]. Kiyami and colleagues [69] assessed differences in functional connectivity of the sensorimotor network during in-phase and antiphase bilateral finger tapping. In young adults, inter- and intra-hemispheric task-specific connectivity is modulated by left dorsal premotor area (PMd) during in-phase and antiphase tasks.…”
Section: Changes In Cortical Contributionsmentioning
confidence: 99%
“…In young adults, inter- and intra-hemispheric task-specific connectivity is modulated by left dorsal premotor area (PMd) during in-phase and antiphase tasks. Older adults, in contrast, demonstrated reduced task specific interhemispheric connections of left PMd during both tasks, while intrahemispheric connectivity from left PMd to left M1 was increased during the in-phase task [69]. Given the role of the PMd for motor planning and monitoring, these findings also suggest that older adults may have deficits in these processing stages, rather than motor execution.…”
Section: Changes In Cortical Contributionsmentioning
confidence: 99%